Análise do genoma e do potencial de virulência de uma cepa de Escherichia coli uropatogênica portadora de marcadores de e. Coli diarreiogênica - Valiatti, Tiago Barcelos [UNIFESP] (2019)
Urinary tract infection is one of the most prevalent in the world, with uropathogenic Escherichia coli (UPEC) being its main agent. Although E. coli strains can receive genes encoding virulence factors by horizontal transfer, little is known about the occurrence of virulence genes of diarrheagenic E. coli (DEC) in UPEC strains. In a previous study, our laboratory identified an UPEC strain (UPEC 252)that carrieed the eae gene, which encodes an adhesive protein (Intimin), is located in the pathogenicity island termed LEE (locus of enterocyte effacement) and is a diagnostic marker of two DEC pathotypes: enteropathogenic E. coli (EPEC) and enterohemorrhagic E. coli (EHEC). The presence of the LEE region indicates the ability of the bacteria to cause attaching-effacing (A/E) lesions in enterocytes. This project aimed to analyze the genome and the pathogenic potential of the UPEC 252 strain. To that end, its total genome was sequenced, and phenotypic virulence and antimicrobial resistance assays were conducted. To evaluate the role of intimin in its pathogenicity, an UPEC 252 mutant strain in the eae gene was constructed and evaluated. The in vitro analysis of the UPEC 252 genome for the presence of 118 virulence genes of the different E. coli strains revealed the occurrence of ompA, mat, fimA, traT, cvpA, focA, fhuA, fhuE, tonB, fepA, astA, celB, iss, air, malX, clb, astA, ecpA, hcpA and csgAB. The presence of all the genes that make up the LEE region and seven genes collectively known as non-LEE (cif, nleF, nleH, nleE, nleB, nleG and espJ) were also identified. The functionality of the LEE region was confirmed by immunoblotting for the Intimin and EspB proteins. In addition, assays performed to identify the ability to polymerize actin filaments (FAS) revealed the ability of UPEC 252 to promote A/E lesion in HeLa cells. UPEC 252 presented a heterogeneous adherence pattern, with bacteria adhered randomly, occasionally forming loose microcolonies in HeLa cells. Phenotypic tests showed that UPEC 252 is resistant to the bactericidal power of human serum, does not produce biofilm and is sensitive to all antimicrobials tested. The eae mutant strain constructed (UPEC 252 Δeae) was compared to the wild-type strain in adherence assays in HeLa, T24, HEK 293T, Caco-2 and LS 174T cells. In these assays, it was demonstrated that in the absence of intimin there was a partial decrease of adherence in HeLa, T24 and HEK 293T cells, whereas in intestinal lineages (Caco-2 and LS 174T), there was a strong reduction in the adherence capacity of UPEC 252, suggesting that Intimin is the major adhesin used by UPEC 252 to adhere to these cell lines in vitro. In addition, the invasion tests performed with the UPEC 252 wt and UPEC 252 Δeae strains in the HeLa, HEK 293T and Caco-2 cell lines showed a low percentage of internalized bacteria. The findings observed in this study suggest that UPEC 252 is potentially more virulent, because it presents a hybrid genome, sharing functional virulence genes characteristic of ExPEC and DEC, which would allow it to cause disease in the intestinal and extraintestinal sites.